Ethno-medico documentation of medicinal plants in Madanapalle mandal of Chittoor District, Andhra Pradesh - Goli Penchala Pratap; Mohd Kashif Husain; Munawwar Hussain Kazmi; G Sudarsanam; G R Prasad (Wolters Kluwer Medknow Publications, 2019)
Background: The present study was conducted in Madanapalle mandal of Chittoor District, of Andhra Pradesh. Since the ages, the studied areas have been inhabited by tribal groups of three types; Yanadi, Chenchu and Sugali. These tribals settled in thick forest zones and not much aware about the lifestyle of urban civilization. They attain their day-to-day needs like food, medicine, fabrics and shelter from nature only. Tribal people have obtained good therapeutic knowledge on trial and error basis with their each day experiences to deal with some health related problems. With this background, the present study was undertaken to document the traditional ethno-medicinal knowledge. Objective: The main objective of this study is to document the first-hand information on age old therapeutic knowledge of tribal and rural people of the Madanapalle mandal of Chittoor District of Andhra Pradesh. Materials and methods: Folklore information on therapeutic practices was collected by the conversation with traditional healers, tribal doctors and elder people during the field trips on the basis of interviews, through which local names, plant parts (used), the method of preparation and dosage were recorded. The plants were systematically authenticated with the support of related flora. Results: The study revealed 46 folk-therapeutic claims upon 41 species belonging to 38 genera (Angiosperms) of 26 families against 24 types of disease conditions. Conclusion: The folklore knowledge on herbal therapies is still in-practice among the tribal communities and rural people of the studied area. Scientific validation of these claims by the advanced scientific studies may provide new drugs of natural origin.